Konseling Kelompok untuk Meningkatkan Perilaku Tanggung Jawab Peserta Didik Kelas IX SMP YPS Singkole dengan Pendekatan SFBC - Bulan, Deviyanti Rezky; Samad, Sulaiman; Rosmini, Rosmini (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
This activity aims to increase the responsible behavior of ninth-grade students of SMP YPS Singkole. The design used group counseling with a solution-focused brief counseling approach (questioning technique). This activity involved a guidance and counseling teacher with six students. The stages in this activity were the initial stage, the intermediate stage, the core stage, and the final stage. The group counseling process is initiated by identifying problems, setting goals, designing interventions using questioning techniques, and assigning strategies for sustaining changes. Subsequently, identifying indicators of behavior change and motivating students so that behavior change remains constant, and evaluating them as the final stage of counseling. Thus, students were able to enhance responsible behavior in learning during the COVID-19 pandemic.